2001
DOI: 10.1093/jn/131.10.2628
|View full text |Cite
|
Sign up to set email alerts
|

Retinoic Acid and Lipopolysaccharide Act Synergistically to Increase Prostanoid Concentrations in Rats In Vivo

Abstract: Vitamin A and its active metabolite retinoic acid (RA) modulate host-pathogen interactions by interfering with the host immune and inflammatory response including prostaglandin (PG) biosynthesis. The effects of RA on phospholipase A(2) (PLA(2)) and cyclooxygenase (COX) isoforms in vitro are controversial, and few in vivo studies exist. We investigated the in vivo effects of RA on PG biosynthesis in the presence or absence of lipopolysaccharide (LPS) in rats. RA alone [10 mg/(kg. d) for 5 d] increased plasma an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 35 publications
2
13
0
Order By: Relevance
“…A single dose per day was chosen, instead of multiple doses, since it has been shown that a much better tolerance of retinoic acid is observed when using single doses [31]. Furthermore, the doses used in the present study have been shown to have anti-inflammatory properties in experimental models of nephropathy [21], and also to induce an increment in the prostaglandin E2 concentration in rats [4]. They were also well below the doses described as toxic in similar species [31].…”
Section: Discussionmentioning
confidence: 92%
See 2 more Smart Citations
“…A single dose per day was chosen, instead of multiple doses, since it has been shown that a much better tolerance of retinoic acid is observed when using single doses [31]. Furthermore, the doses used in the present study have been shown to have anti-inflammatory properties in experimental models of nephropathy [21], and also to induce an increment in the prostaglandin E2 concentration in rats [4]. They were also well below the doses described as toxic in similar species [31].…”
Section: Discussionmentioning
confidence: 92%
“…The regulation of the synthesis of prostaglandins by ATRA is also controversial in in vitro preparations. However, using a similar protocol of administration of ATRA in rats, it has been shown that retinoic acid increases plasma and liver prostaglandin concentrations, especially prostaglandin E2, by increasing COX-1 protein expression and this enhancement is much greater in the presence of lipopolysaccharide [4]. It is well documented that COX enzymes and prostaglandins are involved in the central processing of nociceptive information (see for example [34], and references within), and especially in situations of inflammation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports show that liver injury or inflammation increases the local PGE 2 concentration in sinusoids up to several hundred or thousand nanomolar (Neuschafer‐Rube et al. , 1993; Devaux et al. , 2001).…”
Section: Discussionmentioning
confidence: 99%
“…For instance, ATRA treatment enhances TRPV1 protein expression and function in TRPV1-expressing SHSY5Y neuroblastoma cells (66). Retinoid signaling can also influence levels of other proinflammatory mediators, such as NGF and prostaglandins, which could change pain sensation under disease conditions such as diabetes mellitus (62,67).…”
Section: Figurementioning
confidence: 99%